Evaluation of Severity of Schizophrenia in Tobacco Addicts - ., Washdev; Qamar, Zarmeen; ., Priyanka; Das, Kheenpal; Rajani, Hina; Hashmani, Nauman; Hashmi, Shah Kamal; Ur Rehman, Raza (Journal of Liaquat University of Medical & Health Sciences, 2019)
BACKGROUND: Nicotine use is reported more in Schizophrenic patients as compared to general population, which results is decrease efficacy of psychotropic medicines, thus increased severity of illness. OBJECTIVE: The objective of this study is to evaluate the severity of schizophrenia following tobacco use. METHODOLOGY: This cross-sectional study was conducted at department of Psychiatry Civil Hospital Karachi, Pakistan. Patients were recruited using convenience sampling technique. Clinical symptoms in patients were measured by the 18-item Brief Psychiatric Rating Scale (BPRS), scored 1–7 on each item. RESULTS: Out of the 276 patients included in the study, more than half of the participants were tobacco addicts (n=150, 54%). The statistical analysis showed significant relation (p value=0.04) between the Brief Psychiatric Rating Scale (BPRS) and tobacco addiction. CONCLUSION: This study found that schizophrenia patients with tobacco addiction had worse psychiatric symptoms as compared to those who are not addicted to tobacco.